Oral Health Status and Oral Hygiene Practices among Urban Slum Dwellers in Rawalpindi, Islamabad, Pakistan: Oral Health and Hygiene Practices Among Urban Slum Dwellers - Farrukh Habib, Muhammad; Mahmood, Humaira; Khizar, Anum; Idrees, Sanam; Pervaiz, Farrah; Khan, Jawaria (Pakistan Journal of Health Sciences, 2022)
Poor oral hygiene is a major factor for oral diseases. Urban slums are recognized as a risk group population as the burden of oral diseases is highest among them. Objectives: To evaluate the oral health status of slums using Decayed, Missed, and Filled Tooth index. To evaluate the oral health status of slums using Community Periodontal Index for Treatment Need. Methods: A cross-sectional study was carried out on 385 urban slum people aged between 20 to 50 years. A convenient sampling method was adopted. Data were collected by structured questionnaire included information related to patient’s knowledge, attitude, and behavior towards oral hygiene and interviewed by trained staff. Oral examinations were performed in line with WHO guidelines. After taking informed consent oral examinations were done by fresh graduate and DMFT and CPITN index were evaluated. Results: Study participants were assessed for attitude, knowledge and oral health behavior, 47% had Good Attitude, only 6% had Very Good Knowledge and < 1% had Very Good oral health behavior. Mean DMFT and CPITN score among Slums came 8.91 + 7.627 and 1.93 + 0.971 respectively. More than a third of the slums population required emergency levels dental treatments. Conclusions: The residents of slums have poor oral hygiene and high prevalence of dental caries. Low socioeconomic status, and lack of primary dental care programs and session are main reasons for poor oral health